Branch Retinal Vein Occlusion as a Rare Presentation of Antisynthetase Syndrome - Parida, Swati (Cureus, 2021)
A 52-year-old woman developed branch retinal vein occlusion (BRVO) in her right eye, resulting in blurred vision with visual acuities of 6/9 and 6/6-2 in the affected and unaffected eye respectively (Snellen). The patient was successfully treated with a course of eight intravitreal aflibercept injections, improving binocular visual acuity to 6/6. During the course of her ocular management, she was admitted for acute dyspnoea secondary to interstitial lung disease (ILD). The patient was diagnosed with the antisynthetase syndrome (ASS), testing positive for PL-7 auto-antibodies. ASS may have a systemic association with BRVO; although ASS is a rare condition, it should be suspected and investigated in patients with risk factors, particularly if they present with symptoms of ILD. Early ocular intervention is associated with excellent visual outcomes, and prompt diagnosis and treatment of ASS may potentially reduce risks of further retinal vaso-occlusive episodes.